Microbial roles in cave biogeochemical cycling - Zhu, Hai-Zhen; Jiang, Cheng-Ying; Liu, Shuang-Jiang (Frontiers in Microbiology, 2022)
Among fundamental research questions in subterranean biology, the role of subterranean microbiomes playing in key elements cycling is a top-priority one. Karst caves are widely distributed subsurface ecosystems, and cave microbes get more and more attention as they could drive cave evolution and biogeochemical cycling. Researches have demonstrated the existence of diverse microbes and their participance in biogeochemical cycling of elements in cave environments. However, there are still gaps in how these microbes sustain in caves with limited nutrients and interact with cave environment. Cultivation of novel cave bacteria with certain functions is still a challenging assignment. This review summarized the role of microbes in cave evolution and mineral deposition, and intended to inspire further exploration of microbial performances on C/N/S biogeocycles.